Tissue expression and antibacterial activity of host defense peptides in chicken. Issue 1 (December 2016) - Lee, Mi; Jang, Hyun-Jun; Rengaraj, Deivendran; Yang, Seo-Yeong; Han, Jae; Lamont, Susan; Womack, James
Abstract Background Host defence peptides are a diverse group of small, cationic peptides and are important elements of the first line of defense against pathogens in animals. Expression and functional analysis of host defense peptides has been evaluated in chicken but there are no direct, comprehensive comparisons with all gene family and individual genes. Results We examined the expression patterns of all knowncathelicidins, β-defensins andNK-lysin in multiple selected tissues from chickens.CATH1 through 3 were predominantly expressed in the bone marrow, whereasCATHB1 was predominant in bursa of Fabricius. The tissue specific pattern ofβ-defensins generally fell into two groups.β-defensin1-7 expression was predominantly in bone marrow, whereasβ-defensin 8-10 andβ-defensin 13 were highly expressed in liver.NK-lysin expression was highest in spleen. We synthesized peptide products of these gene families and analysed their antibacterial efficacy. Most of the host defense peptides showed antibacterial activity againstE.coli with dose-dependent efficacy.β-defensin 4 andCATH3 displayed the strongest antibacterial activity among all tested chicken HDPs. Microscopic analyses revealed the killing of bacterium by disrupting membranes with peptide treatment. Conclusions These results demonstrate dose-dependent antimicrobial effects of chicken HDPs mediated by membrane damage and demonstrate the differential tissue expression pattern of bioactive HDPs in chicken and the relative antimicrobial potency of the peptides they encode.